(3fXGe GdeYdheGJ GdeWHb aj GdJSjjQ (B/s - (3fhQj, efjQs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2015)
(3fXQG dCf GdcJGHGJ GdehLhOI aj eLGd fXe GdeYdheGJ JJLg CcKQ Gdi GdJQcjR Ydi fXe GdeYdheGJ GdBdjI GdbQjHI CcKQ ef WdHI GdGYdGe GdBdj hGdLPhY GdeTJQcI GdYdejI,JCJj CgejI JbOje gPG GdcJGH Mhd fXGe GdeYdheGJ YeheG hfXGe GdeYdheGJ GdEOGQjI NUhUG GdPj jge WdHI GdYdhe GdGfSGfjI hGdGLJeGYjI YeheG hYdhe GdJSjjQ NUhUG, MjK JHbi gPg GdaQhY aj MGLI eGSI Gdi eQGLY JJcja eY eG jMJGLhfg aj OQGSJge aj GdYdhe GdGbJUGOjI hYdhe GdJSjjQ hNGUI WdHI GOGQI GdGYeGd GdPjf jgJehf GcKQ HcjajI GSJNOGe GdhSGFd GdJcfhdhLjI GdMOjKI GdeQJHWI HfXe GdeYdheGJ hHGdGYdGe GdBdj dage hJSgjd GdYedjI GdGOGQjI aj efXeGJ GddCYeGd GdNGUI hGdYehejI GVGaI Gdi bWGY GdNOeGJ HeNJda aQhYg(B.s
(3GdeQGLY U(B.207s
Keywords: (3fXGe GdeYdheGJs; (3fXe GdeYdheGJ GdEOGQjIs